Comparative Analysis of Grey Wolf Optimizer-based MPPT System with SEPIC Converter for Stand-Alone PV Applications - Riny Sulistyowati; Wildan Agung Pambudi; rini sulistyowati (LPPM INSTITUT TEKNOLOGI TELKOM PURWOKERTO, 2026)
This paper presents a comprehensive investigation into the design and evaluation of a Grey Wolf Optimizer (GWO)-based Maximum Power Point Tracking (MPPT) system integrated with a Single-Ended Primary Inductor Converter (SEPIC) for stand-alone Photovoltaic (PV) systems. The study aims to assess the optimization performance of the GWO algorithm in comparison with conventional MPPT methods. The hardware-based design of the SEPIC converter achieves an average efficiency of 62.45%, with a controlled error margin of 15.26% and a remarkable output voltage stability of 5 mV. The GWO Algorithm is tailored to pinpoint the optimal operating point of the solar panel, yielding superior power extraction accuracy of 99% and agile tracking with a speed of 2 ms under ideal conditions, and 140 ms under non-ideal conditions. Simulation results demonstrate GWO’s capability to generate up to 2 watts more optimal power than traditional algorithms, across both ideal and non-ideal scenarios. Real-world field tests validate the GWO algorithm’s accelerated convergence, heightened robustness, and unwavering stability under diverse environmental conditions.